(untitled) (Práxis Educativa, 2020)
This text discusses the current configuration of a fascist neoliberal governmentality, which has kept principles from neoliberalism while putting into operation a kind of fascism that is both molar (state) and molecular (daily micro-fascisms). From that, the text problematizes the way that such governmentality has affected everyone’s right to schooling in the present time. Thus, homeschooling is analyzed through Bills now pending in the House of Deputies. Regarding the empirical material, two analytical movements have been pointed out: 1) the articulation of homeschooling with the neoliberal principles of individual freedom and accountability; 2) the constitution of exclusion as a right that triggers two processes: exclusion for otherness reclusion and exclusion for sameness protection. Finally, the shared school setting has been evidenced as something non-appropriable that can produce ways of resisting and re-existing in and with the world. Keywords: Homeschooling. Right to schooling. Governmentality.